1990
DOI: 10.1038/345593a0
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional structure of the free radical protein of ribonucleotide reductase

Abstract: The enzyme ribonucleotide reductase furnishes precursors for the DNA synthesis of all living cells. One of its constituents, the free radical protein, has an unusual alpha-helical structure. There are two iron centres that are about 25 A apart in the dimeric molecule. Tyrosine 122, which harbours the stable free radical necessary for the activity of ribonucleotide reductase, is buried inside the protein and is located 5 A from the closest iron atom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
715
1
2

Year Published

1995
1995
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 853 publications
(741 citation statements)
references
References 54 publications
23
715
1
2
Order By: Relevance
“…This fold is also found in the R2 protein of ribonucleotide reductase (Nordlund et al, 1990). The interface between the a and P chains is extensive, burying 4,068 A* of the solvent-exposed surface of each chain.…”
Section: Overall Structurementioning
confidence: 70%
“…This fold is also found in the R2 protein of ribonucleotide reductase (Nordlund et al, 1990). The interface between the a and P chains is extensive, burying 4,068 A* of the solvent-exposed surface of each chain.…”
Section: Overall Structurementioning
confidence: 70%
“…Previous studies of inhibitors to protein R2 of the one-electron reduction type have suggested at least three possible mechanisms for inhibitor activity: (i) direct accessibility of the inhibitor to the iron/radical site, perhaps mediated by protein conformational flexibility, (ii) long range electron transfer from an interaction site on or close to the protein surface, or (iii) existence of another more accessible free radical in equilibrium with the tyrosyl radical [7,20,21]. At present it is not possible to unambigously distinguish a common dominating mechanism for the different R2 proteins that have been studied.…”
Section: Discussionmentioning
confidence: 99%
“…coli R2 (2.2 A resolution) has shown that the tyrosyl radical/ iron site is deeply buried inside the protein, about 10 ~ distant from the nearest protein surface, and is surrounded by several hydrophobic amino acid residues [7].…”
Section: Introductionmentioning
confidence: 99%
“…16 Residues (bold letters) are invariant in all R2 proteins sequenced so far (Asp139 is a Glu in the Epstein-Barr virus protein). Most of them are iron ligands (#), form the hydrophobic pocket (+) around the tyrosyl radical (*) or are proposed to be involved in the electron transfer mechanism (13).…”
Section: Expression Of 22 B Brucei Nrd B In E Colimentioning
confidence: 99%
“…1). Asp85, Glu116, His119, Glu178, Glu212 and His215 correspond to the iron ligands in mouse and E. coli R2 [7,13,14].…”
Section: Sequence Comparison Of 72 Brucei R2 With Other R2 Proteinsmentioning
confidence: 99%